DETERMINING THE AMOUNT OF FAT, LEAN MATTER AND WATER IN THE BODY OF YOUNG PEOPLE (Scientific journal of the Fergana State University, 2024)
The article describes the amount of fat, lean substance and water in the body of young people and their importance for human health. The article gives recommendations for preventing obesity and its harm to the human body.